2002
DOI: 10.1105/tpc.006437
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of Root Hair Initiation and Expansin Gene Expression in Arabidopsis[W]

Abstract: The expression of two Arabidopsis expansin genes ( AtEXP7 and AtEXP18 ) is tightly linked to root hair initiation; thus, the regulation of these genes was studied to elucidate how developmental, hormonal, and environmental factors orchestrate root hair formation. Exogenous ethylene and auxin, as well as separation of the root from the medium, stimulated root hair formation and the expression of these expansin genes. The effects of exogenous auxin and root separation on root hair formation required the ethylene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

14
352
0
3

Year Published

2006
2006
2018
2018

Publication Types

Select...
4
3
2

Relationship

1
8

Authors

Journals

citations
Cited by 408 publications
(374 citation statements)
references
References 53 publications
14
352
0
3
Order By: Relevance
“…Moreover, expansin proteins localize at the root hair tip (Baluška et al, 2000) in Arabidopsis, and exogenous application of purified expansin proteins will cause the Arabidopsis root hair tip to burst . Previously, we identified two Arabidopsis expansin genes (AtEXPA7 and AtEX-PA18) that contain RHE consensus motifs in their promoter regions ( Cho and Cosgrove, 2002;Kim et al, 2006). Here, we demonstrated that the reduction of the levels of the AtEXPA7 transcript suppresses root hair elongation.…”
Section: Resultsmentioning
confidence: 80%
“…Moreover, expansin proteins localize at the root hair tip (Baluška et al, 2000) in Arabidopsis, and exogenous application of purified expansin proteins will cause the Arabidopsis root hair tip to burst . Previously, we identified two Arabidopsis expansin genes (AtEXPA7 and AtEX-PA18) that contain RHE consensus motifs in their promoter regions ( Cho and Cosgrove, 2002;Kim et al, 2006). Here, we demonstrated that the reduction of the levels of the AtEXPA7 transcript suppresses root hair elongation.…”
Section: Resultsmentioning
confidence: 80%
“…Other genes, like HHD2, regulate root hair elongation through the regulation of various cellular components. Such genes include COW1, MYA2, RHD2, EXPA7, RHS2, RSL2, and ACTIN2 (Cho and Cosgrove, 2002;Ringli et al, 2002;Foreman et al, 2003;Böhme et al, 2004;Peremyslov et al, 2008;Won et al, 2009;Yi et al, 2010). For example, a widely characterized cellular component involved in root hair elongation is ROS, which is produced by NADPH activity.…”
Section: Discussionmentioning
confidence: 99%
“…We first investigated Arabidopsis EXPANSIN7 (AtEXP7) and AtEXP18, which are expressed exclusively in root hairs and have been used as root hair marker genes (Cho and Cosgrove, 2002). The promoter regions of these genes contain a root hair-specific ciselement called RHE (for root hair element), which is functionally conserved among root hair genes in a wide range of angiosperms with distinct root hair distribution patterns (Kim et al, 2006).…”
Section: Expression Of a Root Hair Marker Gene In The Haustoriummentioning
confidence: 99%
“…Similarly, two expansins were up-regulated 6 hpi. Expansins are linked to root hair initiation in Arabidopsis and barley (Hordeum vulgare) and may be related to the reinitiation of polar growth during root hair branching (Cho and Cosgrove, 2002;Kwasniewski and Szarejko, 2006). Additionally, several b-glucanases were induced by 6 hpi.…”
Section: Early Induction Of Genes Involved In Polar Root Hair Growthmentioning
confidence: 99%